2016
DOI: 10.2147/ijn.s115037
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin and gambogic acid coloaded cysteamine-CdTe quantum dots minimizing the multidrug resistance of lymphoma in vitro and in vivo

Abstract: To minimize the side effects and the multidrug resistance (MDR) arising from daunorubicin (DNR) treatment of malignant lymphoma, a chemotherapy formulation of cysteamine-modified cadmium tellurium (Cys-CdTe) quantum dots coloaded with DNR and gambogic acid (GA) nanoparticles (DNR-GA-Cys-CdTe NPs) was developed. The physical property, drug-loading efficiency and drug release behavior of these DNR-GA-Cys-CdTe NPs were evaluated, and their cytotoxicity was explored by 3-[4,5-dimethylthiazol-2-y1]-2,5-diphenyltetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Our study revealed that PEG-CdTe nanoparticles could load DOX with high DL and EE (Fig. 2e ), which are consistent with other studies [ 12 , 13 ]. Moreover, the PEG-CdTe nanoparticles in diameter of 8.2 nm (< 10 nm) could be quickly metabolized by the urinary system [ 23 ], and PEG-CdTe-DOX nanoparticles in size of 78.31 nm (< 200 nm) prolonged the blood circulation time and reduced or even avoided plasma opsonization and absorption in the reticuloendothelial system [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study revealed that PEG-CdTe nanoparticles could load DOX with high DL and EE (Fig. 2e ), which are consistent with other studies [ 12 , 13 ]. Moreover, the PEG-CdTe nanoparticles in diameter of 8.2 nm (< 10 nm) could be quickly metabolized by the urinary system [ 23 ], and PEG-CdTe-DOX nanoparticles in size of 78.31 nm (< 200 nm) prolonged the blood circulation time and reduced or even avoided plasma opsonization and absorption in the reticuloendothelial system [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…PEG-CdTe QDs are efficiently internalized by cells through the fluid phase endocytosis and the lipid bilayer affinity on the plasma membrane surface [ 18 ]. As a drug nanoparticles vehicle, drugs loaded CdTe QDs can release drugs in a pH-controlled and pH-triggered pattern, and these nanoparticle complexes can release drugs at low pH that is similar to the tumor microenvironment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is used in the clinic to treat leukemia and lymphoma, which are at the origin of some cell lines that we have used in our study. Finally, like other anthracyclines, it is exported from cells by a broad range of transporters [ 34 ]. We used OCI-AML3 cells treated for one week with 1 mM and 5mM DCA or growing in OXPHOS medium.…”
Section: Resultsmentioning
confidence: 99%
“… 121 Moreover, Zhou et al synthesized cysteamine-modified cadmium tellurium (Cys-CdTe) quantum dots to load daunorubicin (DNR) and GA to reduce the side effects and multidrug resistance (MDR) generated from DNR chemotherapy of malignant lymphoma, which could down-regulate the expression of P-glycoprotein on Raji/DNR cells resulting in minimizing MDR. 134 It was reported that GA and DTX could simultaneously release from PLGA nanoparticles, showing the synergistic antitumor effect attributed to the reversion of multidrug resistance of MCF-7/ADR cells to DTX and inducing cell apoptosis through downregulating the expression of P-gp. 126 …”
Section: Combination Therapymentioning
confidence: 99%